Dependence of Aerosol‐Droplet Partitioning on Turbulence in a Laboratory Cloud. Issue 5 (11th March 2021) - Shawon, Abu Sayeed Md; Prabhakaran, Prasanth; Kinney, Greg; Shaw, Raymond A.; Cantrell, Will
Abstract: Activation is the first step in aerosol‐cloud interactions, which have been identified as one of the principal uncertainties in Earth's climate system. Aerosol particles become cloud droplets, or activate, when the ambient saturation ratio exceeds a threshold, which depends on the particle's size and hygroscopicity. In the traditional formulation of the process, only average, uniform saturation ratios are considered. However, turbulent environments like clouds intrinsically have fluctuations around mean values in the scalar fields of temperature and water vapor concentration, which determine the saturation ratio. Through laboratory measurements, we show that these fluctuations are an important parameter that needs to be addressed to fully describe activation. Our results show, even for single‐sized, chemically homogeneous aerosols, that fluctuations blur the correspondence between activation and a particle's size and chemical composition, that turbulence can increase the fraction of aerosol particles which activate, and that the activated fraction decreases monotonically as the concentration of aerosol increases. Taken together, our data demonstrate that fluctuations can have effects equivalent to the aerosol limited and updraft limited regimes, known from adiabatic parcel theory. Plain Language Summary: Formation of cloud droplets occurs when the relative humidity exceeds a threshold value, inducing condensation of water vapor onto preexisting aerosol particles. Which of the preexisting particles become cloud droplets depends on their size and chemical composition. In the conventional view of the process, only the average value of the relative humidity is considered. Our laboratory experiments show that fluctuations, caused by turbulence, must also be considered. These fluctuations can increase the fraction of aerosol particles which become cloud droplets and in general, can mimic the effect of heterogeneity in size and chemical composition of aerosol particles. Key Points: Turbulence blurs the relationship between activation and aerosol size and chemical composition Turbulence can increase the fraction of aerosol particles that are activated For a given supersaturation forcing, activated fraction decreases monotonically as aerosol loading increases